Use of fluorescent oligonucleotide probes for differentiation between Paracoccidioides brasiliensis and Paracoccidioides lutzii in yeast and mycelial phase - Thales Domingos Arantes; Raquel Cordeiro Theodoro; Marcus de Melo Teixeira; Eduardo Bagagli (Memorias do Instituto Oswaldo Cruz)
BACKGROUND Fluorescence in situ hybridisation (FISH) associated with Tyramide Signal Amplification (TSA) using oligonucleotides labeled with non-radioactive fluorophores is a promising technique for detection and differentiation of fungal species in environmental or clinical samples, being suitable for microorganisms which are difficult or even impossible to culture. OBJECTIVE In this study, we aimed to standardise an in situ hybridisation technique for the differentiation between the pathogenic species Paracoccidioides brasiliensis and Paracoccidioides lutzii, by using species-specific DNA probes targeting the internal transcribed spacer-1 (ITS-1) of the rRNA gene. METHODS Yeast and mycelial phase of each Paracoccidioides species, were tested by two different detection/differentiation techniques: TSA-FISH for P. brasiliensis with HRP (Horseradish Peroxidase) linked to the probe 5’ end; and FISH for P. lutzii with the fluorophore TEXAS RED-X® also linked to the probe 5’ end. After testing different protocols, the optimised procedure for both techniques was accomplished without cross-positivity with other pathogenic fungi. FINDINGS The in silico and in vitro tests show no reaction with controls, like Candida and Cryptococcus (in silico) and Histoplasma capsulatum and Aspergillus spp. (in vitro). For both phases (mycelial and yeast) the in situ hybridisation showed dots of hybridisation, with no cross-reaction between them, with a lower signal for Texas Red probe than HRP-TSA probe. The dots of hybridisation was confirmed with genetic material marked with 4’,6-diamidino-2-phenylindole (DAPI), visualised in a different filter (WU) on fluorescent microscopic. MAIN CONCLUSION Our results indicated that TSA-FISH and/or FISH are suitable for in situ detection and differentiation of Paracoccidioides species. This approach has the potential for future application in clinical samples for the improvement of paracoccidioidomycosis patients prognosis.